Improving Midwifery Education: A Strategic Approach to Strengthening Character Development for Professional Excellence - Kursih Sulastriningsih; Iim Wasliman; Rita Sulastini; Sri Handayani (CV. Media Digital Publikasi Indonesia, 2026)
Character education in midwifery is essential, as the profession demands not only academic competence but also ethical conduct in providing health services. Midwifery professionals must embody high integrity, empathy, professionalism, and the ability to maintain dignity. However, the integration of character education into midwifery education remains insufficient because of challenges, such as inadequate curriculum integration, limited teaching resources, lack of field experience, and ineffective character evaluation. This study utilizes George Robert Terry’s management principles and Thomas Lickona’s character education framework, alongside Ministry of Health standards, to analyze the management of Character Education Strengthening (CES) in improving graduate quality at the DIII Midwifery Program at Universitas Faletehan Banten and STIKes Widya Dharma Husada Tangerang. Using a qualitative case study approach, the data were collected through interviews, observations, and documentation. The results showed that systematic CES management, encompassing planning, organising, implementing, and evaluating, significantly enhances both the character and competence of midwifery graduates, aligning them with professional standards and ethics. Challenges such as limited human resources and resistance to character education integration can be addressed by enhancing lecturer training and raising awareness of its importance for community services. Therefore, operational standards for midwifery character education are essential for producing graduates who excel academically and possess strong professional ethics, benefiting both the profession and society.